1980
DOI: 10.1093/oxfordjournals.aje.a113039
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of the Epidemiology of Psychoses in Croatia, Yugoslavia

Abstract: This is the fourth paper in a series on the epidemiology of psychoses in Croatia, Yugoslavia. Data collected from 1960-1975 on a representative sample of the population of the study area, including the Istrian Peninsula and the northern Adriatic littoral, and the control area, the rest of Croatia, indicate that functional psychotic illnesses are more frequent in the study area, with the highest rates in older population groups. The finding is not associated with coastal or inland residence, with educational le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly high rates of schizophrenia have been reported in parts of Croatia (Crocetti et al, 1964;Lemkau et al, 1971). But a recent study (Folnegovic and Folnegovic-Smalc, 1992) aimed at investigating differences in prevalence rates in different parts of Croatia concluded that economic migration and negative selection in the domestic population were likely to be the most significant factors in differences in prevalence.…”
Section: Constancy Of Incidence Over Time and Place: 'The Anthropo-pamentioning
confidence: 85%
“…Similarly high rates of schizophrenia have been reported in parts of Croatia (Crocetti et al, 1964;Lemkau et al, 1971). But a recent study (Folnegovic and Folnegovic-Smalc, 1992) aimed at investigating differences in prevalence rates in different parts of Croatia concluded that economic migration and negative selection in the domestic population were likely to be the most significant factors in differences in prevalence.…”
Section: Constancy Of Incidence Over Time and Place: 'The Anthropo-pamentioning
confidence: 85%
“…At the 1982 and 2006 examinations we used the same method as in 1972, described elsewhere (12). (13)(14)(15). The participants had to score from one to fi ve the consumption of ten food 1 groups * : preserved meat, fresh meat, fi sh (mainly pelagic), cooked vegetables, fresh fruit and vegetables, legumes, potatoes, pastry and rice, cookies and sweets, bread, and dairy products.…”
Section: Methodsmentioning
confidence: 99%
“…These reported the results of 18 unique primary investigations of prevalence of schizophrenia and related disorders. Table 1 documents our reasons for excluding those prevalence studies fulfilling all but 1 inclusion criterion (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Of the 53 papers reporting incidence, 44 were excluded; 40 studies did not meet eligibility criteria, and 4 reported duplicate data.…”
Section: Description Of Studiesmentioning
confidence: 99%